A promising sword of tomorrow: Human γδ T cell strategies reconcile allo-HSCT complications. Issue 3 (May 2016) - Hu, Yongxian; Cui, Qu; Luo, Chao; Luo, Yi; Shi, Jimin; Huang, He
Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is potentially a curative therapeutic option for hematological malignancies. In clinical practice, transplantation associated complications greatly affected the final therapeutical outcomes. Currently, primary disease relapse, graft-versus-host disease (GVHD) and infections remain the three leading causes of a high morbidity and mortality in allo-HSCT patients. Various strategies have been investigated in the past several decades including human γδ T cell-based therapeutical regimens. In different microenvironments, human γδ T cells assume features reminiscent of classical Th1, Th2, Th17, NKT and regulatory T cells, showing diverse biological functions. The cytotoxic γδ T cells could be utilized to target relapsed malignancies, and recently regulatory γδ T cells are defined as a novel implement for GVHD management. In addition, human γδ Τ cells facilitate control of post-transplantation infections and participate in tissue regeneration and wound healing processes. These features potentiate γδ T cells a versatile therapeutical agent to target transplantation associated complications. This review focuses on insights of applicable potentials of human γδ T cells reconciling complications associated with allo-HSCT. We believe an improved understanding of pertinent γδ T cell functions would be further exploited in the design of innovative immunotherapeutic approaches in allo-HSCT, to reduce mortality and morbidity, as well as improve quality of life for patients after transplantation.